2001
DOI: 10.1177/152574010102200403
|View full text |Cite
|
Sign up to set email alerts
|

Use of Brown's 14 Grammatical Morphemes by Bilingual Hispanic Preschoolers

Abstract: This pilot study investigated Standard American English (SAE) morphological development for 15 bilingual Hispanic preschoolers who were attending a bilingual day care center. Participants included nine girls and six boys between the ages of 2.6 years and 5.0 years (mean age = 3.8 years). Thirty-minute spontaneous language samples were obtained, yielding 100 utterances for mean length of utterance (MLU) and morphological analysis according to Miller's (1981) criteria. Analysis of the data revealed emergent use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…In general, the studies found that DLLs’ abilities to produce morphological and syntactic targets were less accurate than monolinguals, but that DLLs’ generally followed the same pattern of development as monolinguals (Bland-Stewart & Fitzgerald, 2001; Bonnesen & Chilla, 2011; Nicholls, Eadie, & Reilly, 2011; Nicoladis & Marchak, 2011; Paradis, Nicoladis, Crago, & Genesee, 2010). Also, it was concluded that difference in the amount of input that DLLs receive in their individual languages explained the differences between DLLs and monolinguals accuracy in producing various grammatical structures (Bonnesen & Chilla, 2011; Nicholls et al, 2011; Paradis et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…In general, the studies found that DLLs’ abilities to produce morphological and syntactic targets were less accurate than monolinguals, but that DLLs’ generally followed the same pattern of development as monolinguals (Bland-Stewart & Fitzgerald, 2001; Bonnesen & Chilla, 2011; Nicholls, Eadie, & Reilly, 2011; Nicoladis & Marchak, 2011; Paradis, Nicoladis, Crago, & Genesee, 2010). Also, it was concluded that difference in the amount of input that DLLs receive in their individual languages explained the differences between DLLs and monolinguals accuracy in producing various grammatical structures (Bonnesen & Chilla, 2011; Nicholls et al, 2011; Paradis et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Spanish speaking children learning English for example acquire some but not all of the grammatical structures expected relative to their MLU (Bland-Stewart & Fitzgerald, 2001). There are cross-linguistic influences that facilitate the acquisition of some structures but inhibit the acquisition of others.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linguistic similarity in the structure, early age-of-acquisition of the progressives and verb selection in the BESA test (walking, skating, swimming, riding) may have facilitated progressives' overall production in our sample. This was evidenced by a higher proportion of partially correct responses as compared to non-target responses in the more complex English passives [64].…”
Section: Discussionmentioning
confidence: 93%